Strange hadron production in Au+Au collisions at sNN =7.7, 11.5, 19.6, 27, and 39 GeV - STAR Collaboration (Physical Review C, 2020)
We present STAR measurements of strange hadron (K0S, Λ, ¯¯¯Λ, Ξ−, ¯¯¯Ξ+, Ω−, ¯¯¯Ω+, and ϕ) production at midrapidity (|y|<0.5) in Au+Au collisions at √sNN = 7.7–39 GeV from the Beam Energy Scan Program at the Relativistic Heavy Ion Collider (RHIC). Transverse-momentum spectra, averaged transverse mass, and the overall integrated yields of these strange hadrons are presented versus the centrality and collision energy. Antibaryon-to-baryon ratios (¯¯¯Λ/Λ, ¯¯¯Ξ+/Ξ−, ¯¯¯Ω+/Ω−) are presented as well and used to test a thermal statistical model and to extract the temperature normalized strangeness and baryon chemical potentials at hadronic freeze-out (μB/Tch and μS/Tch) in central collisions. Strange baryon-to-pion ratios are compared to various model predictions in central collisions for all energies. The nuclear modification factors (RCP) and antibaryon-to-meson ratios as a function of transverse momentum are presented for all collision energies. The K0S RCP shows no suppression for pT up to 3.5 GeV/c at energies of 7.7 and 11.5 GeV. The ¯¯¯Λ/K0S ratio also shows baryon-to-meson enhancement at intermediate pT (≈2.5 GeV/c) in central collisions at energies above 19.6 GeV. Both observations suggest that there is likely a change of the underlying strange quark dynamics at collision energies below 19.6 GeV.
52 citations (Crossref) [2023-10-31] tex.ids: adamStrangeHadronProduction2020 tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85092797509 type: Article
Keywords: dept.phy; peer-reviewed